Landlord Elites on the Dutch Housing Market: Private Landlordism, Class, and Social Inequality. (8th August 2022) - Hochstenbach, Cody
Abstract: The past decade has seen a revival of private renting across a wide range of countries and housing regimes. Economic and housing restructuring has enhanced rental housing's appeal as an investment class. Apart from an increase in investment from firms, institutions, and trusts, this has triggered a revival of private landlordism among individuals and households. Yet, few detailed studies on the social, demographic, and economic profiles of landlords exist. To fill this gap and understand landlords' class position, this article draws on Dutch register data with information on the entire Dutch population and housing stock. Analyses of their socioeconomic characteristics reveal the highly privileged class position of many landlords, with a substantial portion found in top income, wealth, and neighborhood positions. One-third of the top wealth percentile—the Dutch top 1 percent—consists of landlords, underscoring their vast economic power. Although landlords with larger housing portfolios are notably more affluent, small-scale landlords are also highly overrepresented in the upper economic strata. Fundamentally, this article's findings urge us to consider landlordism specifically, and housing more broadly, in terms of class formation and delineation, with a class of landlord elites mobilizing multiple properties for the purpose of wealth accumulation and class reproduction.